A methacrylic hyaluronic acid derivative for potential application in oral treatment of celiac disease. (2nd September 2017) - Pitarresi, Giovanna; Palumbo, Fabio Salvatore; Triolo, Daniela; Fiorica, Calogero; Giammona, Gaetano
Abstract: Objective: Aim of this work was the synthesis of a methacrylic hyaluronic acid (HA) derivative and the production, via photocrosslinking, of related hydrogels loaded with an endopeptidase intended for a potential oral treatment of celiac disease. Methods: The methacrylic derivative of HA was prepared through a one-pot procedure involving the reaction with ethylenediamine (EDA) and methacrylic anhydride (MA). The obtained derivative, named HA-EDA-MA, was used to prepare photocrosslinked hydrogels loaded with a prolyl endopeptidase derived from Flavobacterium meningosepticum (PEP FM) able to detoxify gliadin. Obtained hydrogels were recovered as gels or freeze-dried powders. Results: Hydrogels obtained as freeze-dried powders, are able to protect loaded enzyme from degradation due to freeze-drying process and from alteration during storage, overall in the presence of a cryoprotectant. All photocrosslinked HA-EDA-MA hydrogels (gels and powders) release PEP FM in simulated intestinal fluid in sustained manner and in active form. HA-EDA-MA hydrogels are nontoxic as demonstrated through in vitro studies on BALB 3T3 cells. Conclusions: Prepared hydrogels show a potential application for oral treatment of celiac disease thanks to the possibility to release enzymes able to detoxify the gliadin peptide that induces the immunogenic response.